Physical Education as a Colonial and Neoliberal Category: Transiting Towards the Thinking of Human Motricity in and from Abya Yala - Toro-Arevalo, S (FORO EDUCACION FISICA, ACT FISICA RECREATIVA & DEPORTE CASTILLA & LEON, 2021)
In this article we present a critique of the Chilean and Latin American educational system from the concepts of neoliberalism and modernity as a civilizing project focused on the denial of otherness. From there we justify the impossibility of a Physical Education that, as physical, separates, excludes and denies the various ways of living. We end up proposing human motricity as an ontological and epistemological alternative, understood as the capacity-condition of making-the world, from which it is possible to think about the educational.